Sexual Victimization and Sex-Related Drinking Motives: How Protective is Emotion Regulation?. Issue 2 (12th February 2019) - Bird, Elizabeth R.; Stappenbeck, Cynthia A.; Neilson, Elizabeth C.; Gulati, Natasha K.; George, William H.; Cooper, M. Lynne; Davis, Kelly Cue
Abstract : One in five college women experience sexual victimization (SV), and SV severity is associated with subsequent psychological distress, including sex-related distress. SV severity may also be associated with drinking motives to cope with sex-related distress and to enhance sex (sex-related drinking motives [SRDMs]), particularly if individuals suffer from emotion regulation (ER) difficulties. College women ( N  = 151) completed a survey assessment of ER, SV history, childhood sexual abuse (CSA), and SRDMs. Twelve regression models assessed six facets of ER as moderators between SV severity and SRDMs. Among women with no or low levels of prior SV severity, women with greater access to ER strategies were less likely to endorse drinking to cope SRDMs. At higher levels of SV severity, women at all levels of access to ER strategies were equally likely to endorse drinking to cope SRDMs, suggesting that access to ER strategies did not mitigate motivations to drink to cope with sex-related distress for these women. Women with severe SV histories may benefit from interventions that build on existing ER strengths or address other factors. However, greater access to ER strategies may serve as a protective factor against SRDMs when SV severity is low.